PENINGKATAN PENGETAHUAN DAN KETERAMPILAN IBU BALITA DALAM DETEKSI STUNTING DAN PENENTUAN STATUS GIZI - Galih Purnasari; Yoswenita Susindra (P3M Universitas Aisyiyah Surakarta, 2022)
Stunting was a disruption growth problems because of deficiency nutritional intake in a long periode and unappropriate feeding practice. Riskesdas stated that Bondowoso’s stunting rate was still the third highest in East Java. The stunting rate in Bondowoso was 38% of total childrens under five, meanwhile the threshold determined by WHO was 20%. This activity aimed to increase the knowledge about stunting and skills to determine the toddler’s nutritional status of the mother in TK Kartika IX-37 Bondowoso. This activity was conducted among 35 toddler’s mother in TK Kartika IX-37 Bondowoso. The details of the activity were (1) education about stunting;(2) demonstration about anthropometry measurement and read the Z score curve; (3) education about determined the appropriate source of protein. The results of this activity showed an increased in knowledge related to stunting and appropriate protein source for children growth, evidenced by the mothers were able to answer and demonstrated anthropometry measurement correctly.